The Role of Transforming Growth Factor β-1 (TGF β-1) in The Development of Heart Disease Caused by Induction of High Lipid Diet - Tisna Tyasasmaya (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2012)
Cardiovascular diseases are the disorder of artery carrying blood into heart muscle and characterized by thickening, stiffening and constriction of the artery. In spite of cardiovascular disease cases have been knownsince along time ago, the main factor, mechanism, pathogenesis and indicator of the early existence of these diseases are still unknown. Transforming growth factor β-1 (TGF β-1) is a growth factor produced by various cell types which are presumed to be involved in cardiovascular diseases. This research was done to find out the role of TGF β-1 in cardiovascular diseases. Twenty female Sprague Dawley rats, 150 grams of body weight were used in this research. Rats were adapted for seven days, and then divided randomly into two Groups, 10 rats for each.Group I was fed in standard diet containing 5% of saturated fat, while Group II was fed in high fat diet containing 30% of saturated fat. Rats were maintained for two months, corresponding to each diet treatment of both groups and water ad libitum. After two months of the diet, blood was collected from orbital vein and stored into uncoagulated tube for triglyceride measurement. Rats were then killed, neropsied and their heart tissues were collected into tubes containing 10% formaldehyde for histopathologic analysis and immunohistochemistry to see the expression of TGF β-1. The result of blood analysis showed that the average of triglyceride concentration of Group I was 126 mg/dl and 228.1 mg/dl of Group II. After statistically analyzed using student t-test, it showedthat there was a significant difference between Group I and II (P<0,05). Eventhough histopathologic analysis of heart tissue did not show any alteration, the TGF β-1 was expressed in all heart tissue of Group II . Based on the results above, it can be concluded that TGF β-1 is involved in the incidence of cardiovascular disease and it is possible to use TGF β-1 as a diagnosticmarker of cardiovascular disease.Keywords : heart, cardiovascular disease, orbital vein, high fat diet, TGF β-1